(untitled) (Advancements in Homeopathic Research, 2022)
Background Hypertension is the most pervasive disease worldwide causing multiple chronic conditions without apparent symptoms and a complex aetiology. Anger is a critical variable in Essential Hypertension (EHT). In our study, we tried to correlate anger with EHT and tried to treat anger with homeopathic similimum and thereby bringing the hypertension down. Objectives: • To investigate relationship between anger and its components with hypertension (HT). • To evaluate the efficacy of homoeopathic treatment on anger and thereby on Hypertension in comparison with standard treatment. Methodology 300 patients with EHT were screened. 172 (108 men, 64 women) enrolled, two equal groups by simple randomisation were done. Case taking was done and all patients were advised for Dietary approaches to stop HT (DASH), life style modification and antihypertensives as per individual requirements. STAXI-2 scale was applied to measure anger at the beginning and after six months’ study period. One group was given placebo and other defined similimum. They were followed up every two weeks. Results Except state anger & its components all other variables of anger as well as systolic & diastolic BP have remarkably reduced which is statistically significant since p value is <0.001 with 95% confidence interval. Also, 89% patients in intervention arm experienced relief in the symptom of comorbidities. Conclusion Standard antihypertensives have little impact on anger or general psychopathology of patients and no effect whatsoever on comorbidities unlike similimum which treats patient as a whole.